The role of stem cells in the treatment of retinitis pigmentosa: Contemporary insights and future perspectives - Wang Shiqi (BIO Web of Conferences)
Retinitis pigmentosa (RP) is a hereditary degenerative disorder distinguished by the gradual deterioration of retinal pigment epithelium (RPE) cells and photoreceptors. This condition typically presents with gradual night blindness, difficulties in color perception, central vision impairment, and ultimately leads to blindness, predominantly affecting younger individuals. The irreversible loss of retinal cells poses significant challenges in the treatment of RP. Due to their distinctive potential to differentiate into various retinal cell types, stem cells have emerged as a promising therapeutic strategy for RP. Among the categories of stem cells under investigation, embryonic stem cells (ESCs), induced pluripotent stem cells (iPSCs), and mesenchymal stem cells (MSCs) are particularly prominent. In particular, bone marrow-derived MSCs (BM- MSCs) have shown both safety and efficacy in enhancing visual sharpness and retinal thickness in affected individuals. Moreover, recent studies have highlighted the differentiation potential of Müller glial cells into photoreceptor cells, broadening the scope for treatment. The incorporation of advanced bioengineering techniques-such as 3D bioprinting and gene editing-further enhances the prospects for innovative therapies. Despite significant progress in animal experiments and clinical trials, challenges remain, including uncertainties in cellular differentiation and complications arising from multifaceted retinal pathologies. This review aims to synthesize current insights into stem cell therapy for RP, emphasizing both achievements and ongoing challenges in the pursuit of effective treatments.